Sistem Pemantauan Pasang Surut Air Laut Berbasis Internet Of Things di Pantai Kurnia My Darling - Wadly, Fachrid; Ramadhan, Zuhri; -, Muslim; Alfisyahri Sitompul, Dimas (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
Internet of Things technology provides an effective solution for monitoring changes in sea water levels in real-time from a distance. This research aims to design and create a sea level monitoring device based on NodeMCU ESP32 and HC-SR04 sensor that can preserve the mangrove ecosystem at Pantai Kurnia My Darling. The research results show that the IoT-based sea level monitoring instrumentation tool has a high level of accuracy, making it suitable for field testing. The tool has also successfully conducted real-time testing using ThingSpeak and can send notification alerts via WhatsApp. In the future, the data from this research will serve as a standard for creating better tools to monitor mangrove seedlings, ensuring the preservation of mangrove forests.